Interplay of weak noncovalent interactions in alkoxybenzylidene derivatives of benzohydrazide and acetohydrazide: a combined experimental and theoretical investigation and lipoxygenase inhibition (LOX) studies. Issue 4 (24th December 2020) - Ahmed, Muhammad Naeem; Arif, Muneeba; Andleeb, Hina; Ali Shah, Syed Wadood; Arshad, Ifzan; Tahir, Muhammad Nawaz; Rocha, Mariana; Gil, Diego M.
Abstract : Three hydrazide-based Schiff bases have been synthesized and characterized by IR, UV-vis and X-ray diffraction methods. A detail analysis of intermolecular interactions has been performed by Hirshfeld surface analysis and DFT calculations. Abstract : In this study, three new hydrazide-based Schiff bases (1–3 ) have been synthesized via sonication in good to excellent yields 73–90% and mainly characterized by UV-visible, IR, 1 H-NMR and single crystal X-ray diffraction analysis. The crystal structure of compounds 1 and 2 is stabilized by N–H⋯O, C–H⋯O and C–H⋯N hydrogen bonds, as well as C–H⋯π contacts. In addition, weak π⋯π stacking interactions were observed in the structure of 2 . A detailed analysis of the intermolecular interactions that stabilize the crystal packing has been performed by using Hirshfeld surface analysis and energy framework calculations were carried out to analyze and visualize the topology of the supramolecular assembly, indicating that the dispersion energy is dominant over the electrostatic one in the most energetic dimers of both compounds. The interaction energies associated with the noncovalent interactions observed in the crystal structures and the interplay between them have been calculated using DFT calculations. Moreover, these intermolecular interactions were also characterized by using both Bader's quantum theory of atoms in molecules (QTAIM) and NCI plots. The synthesized alkoxybenzylidene analogs of benzohydrazide and acetohydrazide were screened in vitro against soybean lipoxygenase and were found to show better activity than the standard indomethacin. Putative binding modes and comparison of binding interactions in the protein–ligand complex were analyzed by molecular docking studies.